Implementasi Upaya Geopolitik Rusia Di Kawasan Arktik Tahun 2020-2023 - Jihan, Hilmi Nur; Hapsari, Renitha Dwi (Global and Policy Journal of International Relations, 2025)
ABSTRACT This research focuses on exploring the geopolitical strategies implemented by Russia in the Arctic region which is rich in natural resources. The Arctic region, although small and shallow, has huge economic potential, including oil, natural gas and liquefied gas. Various countries, including Russia, Canada, the United States, Norway, and Denmark, compete to secure this territory. By having the largest land mass in the Arctic, Russia actively secures its claims through strategic policies and actions. The 2035 basic principles policy document reflects Russia's geopolitical efforts in the Arctic region, with a focus on economy, infrastructure and security. This research uses qualitative data analysis methods by collecting data from literature to provide an objective description of the situation. Efforts such as natural resource extraction, infrastructure development, and military presence in the Arctic are a major focus, demonstrating Russia's determination to maintain its dominance in the Arctic region. Keywords: Geopolitics, National Policy, Natural Exploitation, Infrastructure, Russian Military ABSTRAK Penelitian ini berfokus pada eksplorasi strategi geopolitik yang diterapkan oleh Rusia di wilayah Arktik yang kaya akan sumber daya alam. Wilayah Arktik, meskipun terkecil dan dangkal, memiliki potensi ekonomi yang besar, termasuk minyak, gas alam, dan gas cair. Berbagai negara, termasuk Rusia, Kanada, Amerika Serikat, Norwegia, dan Denmark, bersaing untuk mengamankan wilayah ini. Dengan memiliki daratan terbesar di Arktik, Rusia aktif mengamankan klaimnya melalui kebijakan dan tindakan strategis. Dokumen kebijakan prinsip dasar 2035 menjadi cerminan dari upaya geopolitik Rusia di wilayah Arktik, dengan fokus pada ekonomi, infrastruktur, dan keamanan. Penelitian ini menggunakan metode analisis data kualitatif dengan mengumpulkan data dari literatur untuk memberikan deskripsi yang objektif tentang situasi tersebut. Upaya seperti ekstraksi sumber daya alam, pengembangan infrastruktur, dan kehadiran militer di Arktik menjadi fokus utama, menunjukkan tekad Rusia untuk mempertahankan dominasinya di kawasan Arktik. Kata Kunci: Geopolitik, Kebijakan Nasional, Eksploitasi Alam, Infrastruktur, Militer Rusia